CURRENT TRENDS IN PROFESSIONAL TRANSLATOR TRAINING - Yana G. Fabrychna (Alfred Nobel University Publisher, 2021)
The objective of this paper is to study the current trends in professional translator training within masters of art in translation study programs of world leading universities. The analysis of study programs represented on the web-sites of Deutscher Akademischer Austauschdienst, European Master's in Translation, Keystone MASTERSTUDIES, MastersPortal, Postgrad is aimed at finding out the important and successful features in the context of teaching translation in the educational domain to studentsphilologists. Aspects and practices of translator training organization and implementation are studied. The analysis results reveal that preparation of professional translators is distinguished by a strong emphasis on practical translation work and is delivered through a combination of practice classes, workshops, translation project management practices, translation internship in close cooperation of universities with translation service providers, clients, organizations for professional translators, partner universities from the countries whose language is studied within the MA program, translation-related software providers. Practice classes and workshops are taught by staff who are professional translators, editors, reviewers, proofreaders, translation managers. Translation project management is realized in the mode of a simulated translation company staffed and run by students and authentic translation projects preparation and delivering. These project methods are an integrated part of the curriculum that earns credit points. Translation internship is arranged in translation agencies home and abroad, under the guidance of freelancers, in international organizations such as the European Parliament, the United Nations, translation departments of governmental and non-governmental institutions, media, cultural funds, museums, art galleries, local businesses and authorities. Affiliate membership of organizations for language practitioners provides students with useful contacts for building career, as well as interview coaching. Academic editions of translation tools familiarize them with terminology databases, translation memory software, computerassisted translation systems. Aspects and practices of MA in translation training under consideration are important from the point of view of translation pedagogy and have a great potential for being incorporated into the process of teaching translation of texts on education issues to students-philologists as they are aimed at increasing employability of graduates in the domain of translation.